Determinants of disclosure in local government financial reports throughout regency/city in North Sulawesi Province - Ginting, Aulia Margaretha; Karamoy, Herman; Morasa, Jenny (Yayasan Widyantara Nawasena Raharja, 2024)
Local Government Financial Reports (or LKPD) is a form of transparency and accountability of regional government as the implementation of regional income and expenditure budget to the stakeholder. Financial reports are presented based on Government Accounting Standard (GAS) in Indonesia where the notes of financial statements become an important element. In the financial reports, local government has an obligation to disclosure important information for stakeholder interest in decision making as well as for public interest information in the needs of information. This study was conducted to examine the determinants of disclosure in local government financial reports throughout regency/city in North Sulawesi Province. The independent variables in this study are regional financial independence ratio, intergovernmental revenue, and leverage. The dependent variable in this study is disclosure in the financial reports. This study uses secondary data generating from audited LKPD by The Audit Board. The population of this study is audited financial reports of regency/city in North Sulawesi Province by The Audit Board. By purposive sampling method, this study uses 60 audited financial reports with fiscal year 2019 to 2022 and apply multiple linier regression analysis. Based on the results, regional financial independence ratio has no effect on the disclosure in the financial reports. Intergovernmental revenue has a positive significant effect on the financial reports. Leverage has a negative significant effect on the disclosure in the financial reports.